PEMANFAATAN HIDROPONIK WICK SYSTEM DALAM BUDIDAYA TANAMAN KHAS LAMPUNG SEBAGAI UPAYA EDUKASI EKOLOGI DI SMP XAVERIUS 4 BANDAR LAMPUNG - Erizal Barnawi; Anjani; Nabila Zahra; Nadia Yunita; Putri Yunita; Ilham Viksa Danuarta; Gusti Ayu Made Renita Sukmawati; Mattew Made Raditya Nanda Putra; Dilla Etika Sari; Alessa Widya Aryudi; Mutiara Putri Syahrani (STKIP Subang, 2026)
Plastic waste is a growing and difficult environmental problem, including in school environments. At Xaverius 4 Junior High School in Bandar Lampung, many plastic bottles have accumulated, disrupting the cleanliness and beauty of the school, while land for greening is also very limited. This community service program aims to provide ecological education by utilizing used plastic bottles as planting containers using a Wick System hydroponics. The activities were carried out through educational sessions, preparing tools and materials, decorating plastic bottles, and practicing planting and arranging the hydroponic installation. As a result, students began to change their perspective on plastic waste, from something previously considered useless to a useful and attractive planting medium. The use of hydroponics became a cost-effective solution for greening the school in a limited space while increasing students' understanding and responsibility towards the environment. Thus, this activity was able to foster a sustainable attitude of caring for the environment among the school community.